Social Capital and Family Planning Indicator in Indonesia: A Fixed Effect Analysis - Alifia Nugrahani Sidhi (The Journal of Indonesia Sustainable Development Planning, 2026)
Despite Indonesia’s family planning initiatives, modern contraceptive use has seen little progress over the past decade. This study investigates how women’s community participation, as a proxy for social capital, influences contraceptive behavior among women of reproductive age in rural and urban areas. Using panel data from the Indonesia Family Life Survey (IFLS) waves 4 and 5, fixed effects regression identifies the causal impact of community engagement. Results show that participation in health-related community groups increases the likelihood of modern contraceptive use by 11.5 percentage points compared to non-participation, while non-health-related activities have no significant effect. No rural–urban differences are observed. Decision-making autonomy and access to accurate contraceptive information strongly predict use, while education shows no consistent effect. These findings highlight the importance of health-related social capital in promoting contraceptive uptake. Policies should strengthen grassroots women’s health networks and integrate them more closely with national reproductive health programs. Keywords: community participation; Indonesia Family Life Survey (IFLS); modern contraceptive use; social capital.